2012
DOI: 10.3389/fnbeh.2012.00084
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting neural activity related to awake-state sharp wave-ripple complexes prevents hippocampal learning

Abstract: Oscillations in hippocampal local-field potentials (LFPs) reflect the crucial involvement of the hippocampus in memory trace formation: theta (4–8 Hz) oscillations and ripples (~200 Hz) occurring during sharp waves are thought to mediate encoding and consolidation, respectively. During sharp wave-ripple complexes (SPW-Rs), hippocampal cell firing closely follows the pattern that took place during the initial experience, most likely reflecting replay of that event. Disrupting hippocampal ripples using electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 35 publications
4
72
0
Order By: Relevance
“…The competing networks hypothesis is further supported by the results of a recent study where ongoing neural activity during the intertrial interval was interrupted by bright flashes of light at times of ripple occurrence in the rabbit (Nokia et al 2012). Salient sensory stimulation in any modality elicits a burst of LC-NE neurons (Foote et al 1980;Herve-Minvielle and Sara 1995).…”
Section: Competing Functional Networkmentioning
confidence: 68%
See 1 more Smart Citation
“…The competing networks hypothesis is further supported by the results of a recent study where ongoing neural activity during the intertrial interval was interrupted by bright flashes of light at times of ripple occurrence in the rabbit (Nokia et al 2012). Salient sensory stimulation in any modality elicits a burst of LC-NE neurons (Foote et al 1980;Herve-Minvielle and Sara 1995).…”
Section: Competing Functional Networkmentioning
confidence: 68%
“…Salient sensory stimulation in any modality elicits a burst of LC-NE neurons (Foote et al 1980;Herve-Minvielle and Sara 1995). In this case, the visual stimulus presented at ripple onset transiently shifted hippocampal activity to the theta-oscillation state and caused impaired acquisition of a trace eye blink conditioning, a hippocampus-dependent associative learning task (Nokia et al 2012). Clearly, introducing any interference to the post-learning information processing either by disruption of activity within the supporting network or by coactivation of competing networks would lead to less efficient consolidation.…”
Section: Competing Functional Networkmentioning
confidence: 99%
“…In 2012, Nokia and colleagues demonstrated the necessity of SPW-R hippocampal events that are characteristic of SWS by disrupting SPW-R with electrical stimulation in rabbits. This manipulation impaired trace eyeblink conditioning, a hippocampus-dependent learning task (Nokia et al 2012). Other studies in humans have shown that reactivation during SWS can enhance not only spatial memory but also procedural memories, suggesting that reintroduction of cues during sleep may reactivate other brain regions as well (Antony et al 2012;Oudiette et al 2013).…”
Section: Sleep Enhances Memory Consolidationmentioning
confidence: 99%
“…The presentation of the auditory cue during SWS increased activation of the medial temporal lobe and altered parahippocampal-medial prefrontal connectivity, which has traditionally been associated with declarative memory (Van Dongen et al 2012). Not only has inducing neuronal replay during SWS been shown to enhance memory consolidation, but also SPW-R disruption impairs hippocampus-dependent memory (Girardeau et al 2009;Nokia et al 2012). In 2012, Nokia and colleagues demonstrated the necessity of SPW-R hippocampal events that are characteristic of SWS by disrupting SPW-R with electrical stimulation in rabbits.…”
Section: Sleep Enhances Memory Consolidationmentioning
confidence: 99%
“…u is thought to reflect a state in which information about the surroundings is actively acquired (Buzsáki 1989). Animals exhibiting dominant hippocampal u during spontaneous recordings prior to training tend to learn better (Berry and Thompson 1978;Nokia et al 2009Nokia et al , 2012b, and high-amplitude, well phase-locked u-band hippocampal responses to the conditioned stimulus early in eyeblink conditioning predict good learning (Nokia et al 2009(Nokia et al , 2010(Nokia et al , 2012aNokia and Wikgren 2014). Training contingent on transient episodes of hippocampal u or its explicit absence has produced significant but somewhat inconsistent effects on learning (Griffin et al 2004;Nokia and Wikgren 2014).…”
mentioning
confidence: 99%